Analisis Minat Penggunaan Fitur Permohonan Layanan Pln Pada Aplikasi New PLN Mobile Dengan Menggunakan Metode TAM 3 - Prasetyohadi, Latif; Suryani, Erma (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2022)
PT PLN (Persero) as a state-owned company with a business in the electricity sector is always trying to improve the quality of service to customers. One of the efforts made is to develop an existing application platform, namely PLN Mobile into New PLN Mobile. As a development from the previous application, PLN has added features for requesting new installation services, changing power, and applying for tariff changes in the New PLN Mobile application. However, with the addition of a new feature, namely the PLN service request feature in the New PLN Mobile application, it will change the PLN service business process that has been running for years. Changes in business processes will affect customer habits in applying for PLN services. This study aims to determine how customer acceptance of the service request feature in the New PLN Mobile application is measured through the intensity (perceived usefulness) and ease of use of the customer. The method used in this research is the distribution of questionnaires followed by statistical analysis using the Technology Acceptance Model (TAM) 3. TAM is a statistical method that combines technology acceptance with a structured equation model. The results obtained are Perceived Usefulness (PU) is influenced by Subjective Norm (SN), Job Relevance (REL), Output Quality (OUT) and Result of Demonstrability (RES), while Perceived Ease of Use (PEOU) is influenced by Perception of External Control (PEC), Computer Anxiety (CANX), Computer Playfulness (CPLAY) and Perceived Enjoyment (ENJ), then Behavioral Intention (BI) is influenced by Perceived Usefulness (PU) and Perceived Ease of Use (PEOU) and Use Behavioral (USE) is influenced by Behavioral Intention (BI). This research is expected to provide input in developing the New PLN Mobile application and improving the quality of PLN services in the future.